2018
DOI: 10.5152/tjar.2018.32748
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Three Methods for Depth of Central Venous Catheter Placement in Children: An Observational Pilot Study

Abstract: Catheter tip placement by external distance or landmark technique is a more accurate method for catheter placement than the Peres and TEE-based formulae. It does not require measurement of patients' height and reduces the chances of repositioning of catheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, people of the same height can have different body habitus that affect the corresponding fixed catheter depth. Many studies suggested that the optimal central line depth was significantly related to the central line curvature within the human body. In this study, a height and a body surface measurement (D) are included in the prediction equation, which is further individualized and useful for wide promotion.…”
Section: Discussionmentioning
confidence: 99%
“…However, people of the same height can have different body habitus that affect the corresponding fixed catheter depth. Many studies suggested that the optimal central line depth was significantly related to the central line curvature within the human body. In this study, a height and a body surface measurement (D) are included in the prediction equation, which is further individualized and useful for wide promotion.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the appropriate length and diameter of the catheter is very important and is determined by several factors, such as the height of the patient and the selected vessel for catheterization 26 . There are several methods available in order to determine the appropriate length of the catheter, such as: Peres formula, TEE formula (trans-oesophangeal) and calculation based on external landmarks 15 • this option was selected for our study. Another critical issue is the determination of the position of the catheter tip.…”
Section: Prevention Of Suboptimal Placementmentioning
confidence: 99%
“…V., Shtilman M. Yu., Chumburidze I. P. tomical landmark widely used in clinical practice [2][3][4][5]. Anatomical variations of the sternal angle have considerable clinical significance.…”
Section: ключевые слова: угол грудины дети ультразвуковое исследованиеmentioning
confidence: 99%